Religion and evolution - Green, Ned M. (My University, 1897)
Introduction: The theory of evolution, which at present is the only scientific way of accounting for the various phenomena of nature, is itself one of the products of evolution. It explains its own existence and that of everything else. It does this, not by calling for acts of special creation or for miracles but by the processes which are going on before our eyes to day. It truths are by no means confined to any one branch of science but are universal and are manifest in all growth and development. The theory in short, so far as the matter of the universe is concerned, is that all planets, suns, and stars and life originated from a great nebula or fire-mist which once filled the space not occupied by the worlds. It holds that all changes tending to bring about these phenomena are going on today and, therefore, asks only for a knowledge of the facts to be observed at the present time to explain the foundation of the worlds and the existence of life. The nebula, on cooling and condensing must have solidified into worlds and stars and, as evidence of this, we know that the smaller planets are now cold while the larger ones are yet hot but rapidly cooling.
Citation: Green, Ned M. Religion and evolution. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Theory of Evolution; Astronomy; Evolution; Theses; Manuscripts (documents)